2023
DOI: 10.1002/slct.202300765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures and Antifungal Activity of Selenoglycolurils

Abstract: A synthetic method for the preparation of selenoglycolurils is reported. Target compounds were obtained by two‐stage transformation of unsubstituted, 1‐substituted and 1,3‐disubstituted thioglycolurils by S‐methylation with MeI to the corresponding isothiouronium salts (Step 1) followed by selenation with NaHSe generated in situ from grey Se and NaBH4 (Step 2). Selenoglycolurils possessed potent antifungal activity against Candida albicans and Cryptococcus neoformans (MIC 0.25–0.125 μg/mL) with no discernable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The completeness of the transformations was controlled by TLC using the same eluent by the disappearance of spots of the starting compounds 4 b , c , 5 a , b and 6 a – c (R f 0.23 for 4 b , 0.35 for 4 c , 0.29 for 5 a , 0.38 for 5 b , 0.11 for 6 a , 0.23 for 6 b , 0.31 for 6 c ) and with 1 H NMR monitoring of dried reaction mixture aliquots for compounds 4 d , 6 d by the disappearance of CH−CH proton signals (s, 5.42 ppm and 5.40 ppm, respectively) [22,23] . It was found that the conditions ( i ) are applicable for the preparation of imidazoimidazothiazole 1 b (yield after isolation 89 %) and imidazoimidazoselenazoles 3 a , b (yields 59 % and 56 %, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The completeness of the transformations was controlled by TLC using the same eluent by the disappearance of spots of the starting compounds 4 b , c , 5 a , b and 6 a – c (R f 0.23 for 4 b , 0.35 for 4 c , 0.29 for 5 a , 0.38 for 5 b , 0.11 for 6 a , 0.23 for 6 b , 0.31 for 6 c ) and with 1 H NMR monitoring of dried reaction mixture aliquots for compounds 4 d , 6 d by the disappearance of CH−CH proton signals (s, 5.42 ppm and 5.40 ppm, respectively) [22,23] . It was found that the conditions ( i ) are applicable for the preparation of imidazoimidazothiazole 1 b (yield after isolation 89 %) and imidazoimidazoselenazoles 3 a , b (yields 59 % and 56 %, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of selenoglycolurils 6 a – d was carried out in 2 stages: first, isothiouronium salts were obtained through S‐methylation of semithioglycolurils 4 a – d with MeI. At the second stage, nucleophilic substitution of the S−Me group with a selenium atom was carried out by the reaction of isothiouronium salts with generated in situ NaHSe [23] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations